Inhibition of cholesterol biosynthesis by fluorinated mevalonate analogues - Reardon, J E; Abeles, R H (Biochemistry (Easton), 1987)
The conversion of mevalonate to cholesterol in rat liver homogenates (IC50 = 0.01-1.0 mM) is inhibited by 6- (I), 6,6-di- (II), and 6,6,6-trifluoromevalonate (III), as well as 4,4-difluoromevalonate (IV). Addition of compound I, III, or IV to rat liver homogenates results in the accumulation of 5-phospho- and 5-pyrophosphomevalonate. The conversion of isopentenyl pyrophosphate to cholesterol is not inhibited by the fluorinated analogues. It thus appears likely that the decarboxylation of mevalonate 5-pyrophosphate is inhibited. Rat liver homogenates catalyze the phosphorylation of I and III. The inhibition of the decarboxylation of mevalonate 5-pyrophosphate by I and III was demonstrated directly with partially purified decarboxylase. Compound I is a remarkably effective inhibitor of the decarboxylation (Ki = 10 nM). Similar results were reported by Nave et al. [Nave, J. F., d'Orchymont, H., Ducep, J. B., Piriou F., & Jung, M. J. (1985) Biochem. J. 227, 247]. It is likely that the phosphorylated or pyrophosphorylated forms of all inhibitors tested are responsible for inhibition. We also describe a chemical method for the synthesis of mevalonate 5-pyrophosphate.